The first complete chloroplast genome of Hovenia acerba Lindl. - Yin, Yanlei (Mitochondrial DNA B Resour, 2020)
Hovenia acerba Lindl. is an important medicinal plant, for which complete chloroplast genome (Accession: MN782301) was sequenced, assembled and annotated. The genome size is 161,668 bp and the overall GC content is 36.69%, with large single-copy (LSC, 89,451bp) regions, small single-copy (SSC, 18,979 bp) regions, and two inverted repeat regions (IRs, 26,619 bp each). A total of 130 genes are successfully annotated, including 85 protein-coding genes, 37 tRNA genes, and 8 rRNA genes. The phylogenetic relationships showed that H. acerba is closely related to the species of Ziziphus genus.